A Preliminary Evaluation of Repeated Exposure for Depersonalization and Derealization. (March 2013) - Weiner, Elliot; McKay, Dean
Dissociative symptoms including depersonalization and derealization are commonly experienced by individuals suffering from panic disorder or posttraumatic stress disorder (PTSD). Few studies have been published investigating the specific treatment of these symptoms in individuals diagnosed with panic disorder or PTSD, despite evidence that the subset of individuals with panic disorder who experience depersonalization and derealization report more panic attacks as well as greater panic severity and functional impairment. Furthermore, it has been shown that these symptoms can impede treatment and recovery in PTSD. Finally, recent research has shown that interoceptive exposure generally enhances the efficacy of treatment outcome for PTSD and PTSD with comorbid panic. This study investigated the use of a novel interoceptive exposure technique for treatment of depersonalization and derealization in individuals with high anxiety sensitivity and/or symptoms of PTSD. Results indicated significant reductions on six of seven items as well as total score on an outcome measure of depersonalization and derealization. Thus, this technique appears to hold promise for utilization as a form of interoceptive exposure in the treatment of these symptoms.